Describing and comparing the characteristics of injured bicyclists and other injured road users: a prospective cohort study - Bamini Gopinath; Jagnoor Jagnoor; Ashley Craig; Annette Kifley; Michael Dinh; Rebecca Ivers; Soufiane Boufous; Ian D. Cameron (BMC, 2016)
Abstract Background We aimed to establish the frequency and characteristics (e.g. socioeconomic, pre-injury, and crash-related parameters) of injured bicyclists and other injured road users. Methods 748 participants aged ≥17 years who had sustained a minor or non-catastrophic injury in a land-transport crash, were interviewed after presenting to a metro hospital emergency department in New South Wales, Australia. A telephone-administered questionnaire obtained information on socio-economic, pre-injury health, and crash-related characteristics. These factors were then compared between injured bicyclists and other road users (car driver/passengers, motorcyclists/pillion and pedestrians/skateboarders). Cycling injury severity was characterized by three metrics (sustaining multiple injuries; hospital admission for ≥12 h; and sustaining a head/neck and/or facial injury). Results In this cohort of people with injuries, 238 (32 %) were bicyclists. Frequency of cycling injuries were significantly different between age-groups among men (p = 0.0002), and were more common in men aged 45-59. Bicyclists were more likely to be aged 45-59, married, have university/tertiary qualifications and have a professional occupation compared to other road users (all p <0.0001). Bicyclists compared to participants involved in other types of land transport crashes were more likely to self-report excellent general health (p = 0.01), and were less likely to report a great/overwhelming perceived danger of death or 15.0 % versus 23-41 %; p <0.0001). Frequency of upper extremity and lower extremity injuries in bicyclists were 81.9 % and 60.5 %, respectively. Explanatory variables significantly associated with injury severity metrics were age, education level, paid work status and perceived danger of death/disability in the crash. Conclusions Minor cycling injuries were a relatively common cause of mild-moderate injury presentations to metro emergency departments. A wide spectrum of socio-demographic-, pre-injury-, and crash-related characteristics were related to cycling injuries.